2019
DOI: 10.1177/2325967119869600
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Clinical Outcomes After Subacromial Spacer Insertion Versus Other Reconstruction Methods in the Treatment of Irreparable Massive Rotator Cuff Tears

Abstract: Background: Previous studies on subacromial spacer (SAS) insertion have been limited to case series that did not compare the effectiveness of this technique with other techniques. Hypothesis: Outcomes after SAS insertion for the treatment of irreparable massive rotator cuff tears (IMRCTs) will be similar to those of other techniques. Study Design: Cohort study; Level of evidence, 3. Methods: This retrospective study was based on data collected from patients who underwent correction of IMRCTs between January 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…54 Another study also concluded that patients with a partial repair and the balloon fared better than those with balloon only intervention. 50 In total 513 patients have been analysed as part of clinical studies investigating the outcome of the subacromial balloon spacer; however, there were 619 patients recruited and included in the studies. Only 83% of patients initially meeting the inclusion criteria were analysed, the majority of the rest were either lost to follow-up or withdrew.…”
Section: Clinical Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…54 Another study also concluded that patients with a partial repair and the balloon fared better than those with balloon only intervention. 50 In total 513 patients have been analysed as part of clinical studies investigating the outcome of the subacromial balloon spacer; however, there were 619 patients recruited and included in the studies. Only 83% of patients initially meeting the inclusion criteria were analysed, the majority of the rest were either lost to follow-up or withdrew.…”
Section: Clinical Resultsmentioning
confidence: 99%
“…Further complications include new-onset pseudoparalysis in two patients following balloon insertion without addressing the associated subscapularis tear. 50 Although the whole biomechanical theory of the InSpace™ balloon is to depress the humeral head inferiorly, thereby recreating native glenohumeral joint kinematics, few studies have analysed the radiographic evidence of this. One of the studies that used plain film radiographs post-operatively concluded that there was no significant effect of the balloon spacer on the upper migration index (UMI) with a pre-op UMI of 1.15 and a post-op of 1.16 52 (UMI < 1.25 is suggestive of severe proximal migration of the humeral head).…”
Section: Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The group in which a procedure other than BSA (biceps augmentation, patch graft, or partial repair alone) was conducted had a higher retear rate (63.9) but similar clinical and radiological results. 27 Bakti et al 28 reported improvements in HRQoL. Physical dimension improved earlier but was nonsignificant at the final follow-up, contrary to mental dimension, which improved markedly only at the final follow-up.…”
Section: Discussionmentioning
confidence: 97%
“…We excluded 398 duplicate articles and further 2017 articles after reviewing the titles and abstracts. After screening the remaining 459 full papers, we included 17 [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] in our network meta-analysis. Figure 1 shows a flowchart of the sample selection procedure.…”
Section: Study Characteristicsmentioning
confidence: 99%